2019
DOI: 10.1002/2211-5463.12734
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of sodium‐glucose cotransporter 2 ameliorates renal injury in a novel medaka model of nonalcoholic steatohepatitis‐related kidney disease

Abstract: The effect of sodium‐glucose cotransporter 2 inhibitor (SGLT2I) on nonalcoholic steatohepatitis (NASH) has been reported, but there are few studies on its effect on NASH‐related renal injury. In this study, we examined the effect of SGLT2I using a novel medaka fish model of NASH‐related kidney disease, which was developed by feeding the d‐rR/Tokyo strain a high‐fat diet. SGLT2I was administered by dissolving it in water of the feeding tank. SGLT2I ameliorates macrophage accumulation and oxidative stress and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The effects of luseogliflozin on BNP and liver function tests agreed with the previous studies 18,19) . The DAPA-HF 20,21) , EMPEROR-Reduced 22,23) , and DEFINE-HF 24) trials showed SGLT2i was effective in reducing HF aggravation risk.…”
Section: Discussionsupporting
confidence: 91%
“…The effects of luseogliflozin on BNP and liver function tests agreed with the previous studies 18,19) . The DAPA-HF 20,21) , EMPEROR-Reduced 22,23) , and DEFINE-HF 24) trials showed SGLT2i was effective in reducing HF aggravation risk.…”
Section: Discussionsupporting
confidence: 91%
“…These giant cells participate in the release of pro-inflammatory agents, which favor the recruitment, accumulation, and activation of new macrophages, which act in the degradation and absorption of biomaterials [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] . Phagocytic cells (F4 / 80 +) have been reported in medaka fish used as a model for inflammation and oxidative stress, describing that positive cells are activated macrophages [55] . During this experiment, we did not observe the complete device biodegradation, possibly due to the short analysis period (120 days), since the time required for PLA biodegradation is estimated to be about 2 years [56] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, among CKD patients participating in the DAPA-CKD clinical trial, those treated with dapagliflozin had better stabilization of GFR and a lower risk of progression to end-stage renal disease or death, again, independent of the presence of diabetes [ 120 ]. Although the renal antioxidant effect of the SGLT2is in nondiabetic human CKD needs to be assessed in future research, studies in nondiabetic experimental models of kidney damage have already shown that these drugs protect the kidney by decreasing oxidative stress [ 121 , 122 ]. Furthermore, SGLT2is also have antioxidant properties in organs other than the kidney.…”
Section: Antioxidant Properties Of Sglt2 Inhibitorsmentioning
confidence: 99%